2018
DOI: 10.1055/s-0037-1621726
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Safety and Efficacy of Regional Anesthesia for Lower Extremity Microvascular Reconstruction: Enhancing Recovery

Abstract: PNC utilization for lower extremity free flap transfer significantly reduced concurrent narcotic use and attained a shorter LOS. The technique provided for safe analgesia during lower extremity free flap reconstructions satisfying the microsurgeon and the anesthesiologist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…An enhanced recovery protocol was utilized for the majority of our patients including the use of regional anesthetic block [9] and an early limb dependency program [10] helped patients dangle early in their postoperative course expediting hospital stay, discharge to rehabilitation facilities, and return toward functional ambulation.…”
Section: Methodsmentioning
confidence: 99%
“…An enhanced recovery protocol was utilized for the majority of our patients including the use of regional anesthetic block [9] and an early limb dependency program [10] helped patients dangle early in their postoperative course expediting hospital stay, discharge to rehabilitation facilities, and return toward functional ambulation.…”
Section: Methodsmentioning
confidence: 99%
“…An enhanced recovery protocol was utilized for the majority of our patients including the use of regional anesthetic block achieved via continuous peripheral nerve catheter placed in the popliteal region targeting the sciatic, tibial and peroneal nerves when appropriate. This achieved decreased rates of postoperative narcotic use and shorter post-anesthesia unit stays [21] . Additionally an early limb dependency program [22] helped patients dangle early in their post-operative course expediting hospital stay, discharge to rehabilitation facilities, and return toward functional ambulation.…”
Section: Reconstructive Techniquementioning
confidence: 96%
“…Numerous studies have demonstrated the efficacy of these blocks in reducing postoperative pain, opioid consumption, and length of hospital stay. 65 67 68 69 70 71 72 73 74 75 76 Transversus abdominis plane blocks in particular are incredibly effective at reducing postoperative abdominal pain and have increasingly become a recommended component of abdominally based autologous breast reconstruction flap enhanced recovery after surgery protocols. 77…”
Section: Breast Surgerymentioning
confidence: 99%